2007
DOI: 10.1063/1.2780868
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear quantum effects on the nonadiabatic decay mechanism of an excited hydrated electron

Abstract: We present a kinetic analysis of the non-adiabatic decay mechanism of an excited state hydrated electron to the ground state. The theoretical treatment is based on a quantized, gap dependent golden rule rate constant formula which describes the non-adiabatic transition rate between two quantum states. The rate formula is expressed in terms of quantum time correlation functions of the energy gap, and of the non-adiabatic coupling. These gap dependent quantities are evaluated from three different sets of mixed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 40 publications
5
48
0
Order By: Relevance
“…We have also found that the non-adiabatic coupling fluctuations are strongly dominated by the librational and vibrational solvent modes. 17,18 We will show in the next section that this is also true for the transition dipole fluctuations. A harmonic bath description (for which the formula is exact) is thus quite sensible, at least for this application.…”
Section: Theoretical Expression Of the Absorption Spectrummentioning
confidence: 91%
See 2 more Smart Citations
“…We have also found that the non-adiabatic coupling fluctuations are strongly dominated by the librational and vibrational solvent modes. 17,18 We will show in the next section that this is also true for the transition dipole fluctuations. A harmonic bath description (for which the formula is exact) is thus quite sensible, at least for this application.…”
Section: Theoretical Expression Of the Absorption Spectrummentioning
confidence: 91%
“…We argued previously that the harmonic quantization scheme was fully justified for quantizing the solvated electron nonadiabatic transition rates. 17,18 We have shown 17 that, for the energy gap fluctuations, this scheme leads to the correct decoherence times for an excited p-electron when compared to the Gaussian packet propagation approach of Prezhdo and Rossky, 38 and Turi and Rossky, 39 both for water and methanol. This argument is still valid for the present application.…”
Section: Theoretical Expression Of the Absorption Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to 2008, many experimental and theoretical studies gave very diverse lifetimes and physical natures of e pre states in liquid water [49][50][51][52][53][54][58][59][60][61][62]. But Wang et al [28] have recently resolved that e pre states are electronically excited states and have lifetimes of ~200 and 500 fs after the identification and removal of a coherent spike effect.…”
Section: More Justification Of the Cosmic-ray-driven-electron-reacmentioning
confidence: 99%
“…In 2000s, Researches on electron solvation dynamics and associated dissociative electron transfer reactions of halogenated molecules have continued in water solution [21,[27][28][29][58][59][60][61][62], ice surface [63], ultrathin ice films [16,17,[64][65][66][67] and H 2 O anionic clusters [68][69][70][71][72][73]. Prior to 2008, many experimental and theoretical studies gave very diverse lifetimes and physical natures of e pre states in liquid water [49][50][51][52][53][54][58][59][60][61][62].…”
Section: More Justification Of the Cosmic-ray-driven-electron-reacmentioning
confidence: 99%